Kidney and urinary tract diseases in the newborn - Alam, Shumyle; Kiessling, Stefan G.; Chishti, Aftab S. (Springer Berlin Heidelberg, 2014)
This book provides a comprehensive and up-to-date overview of all key issues related to kidney and urinary tract disease in full-term and premature newborns. Among the many topics addressed are fluid and electrolyte abnormalities, hydronephrosis, urinary tract infection, obstructive uropathy, and renal replacement therapy. The approach throughout is clinically oriented, the aim being to provide the reader with hands-on guidance. Each chapter commences with a clinical case vignette and concludes with a take-home message highlighting key aspects of practical importance. In addition, however, informative reviews of the literature and the basic sciences are included. No other book currently on the market focuses solely on the newborn, and Kidney and Urinary Tract Diseases in the Newborn will be especially valuable to those undergoing fellowship training in neonatology or pediatric nephrology/urology.